Systemic administration of dendrimer N‐acetyl cysteine improves outcomes and survival following cardiac arrest - Hiren R. Modi; Qihong Wang; Sarah J. Olmstead; Elizabeth S. Khoury; Nirnath Sah; Yu Guo; Payam Gharibani; Rishi Sharma; Rangaramanujam M. Kannan; Sujatha Kannan; Nitish V. Thakor (Wiley, 2022)
Abstract Cardiac arrest (CA), the sudden cessation of effective cardiac pumping function, is still a major clinical problem with a high rate of early and long‐term mortality. Post‐cardiac arrest syndrome (PCAS) may be related to an early systemic inflammatory response leading to exaggerated and sustained neuroinflammation. Therefore, early intervention with targeted drug delivery to attenuate neuroinflammation may greatly improve therapeutic outcomes. Using a clinically relevant asphyxia CA model, we demonstrate that a single (i.p.) dose of dendrimer‐N‐acetylcysteine conjugate (D‐NAC), can target "activated" microglial cells following CA, leading to an improvement in post‐CA survival rate compared to saline (86% vs. 45%). D‐NAC treatment also significantly improved gross neurological score within 4 h of treatment (p < 0.05) and continued to show improvement at 48 h (p < 0.05). Specifically, there was a substantial impairment in motor responses after CA, which was subsequently improved with D‐NAC treatment (p < 0.05). D‐NAC also mitigated hippocampal cell density loss seen post‐CA in the CA1 and CA3 subregions (p < 0.001). These results demonstrate that early therapeutic intervention even with a single D‐NAC bolus results in a robust sustainable improvement in long‐term survival, short‐term motor deficits, and neurological recovery. Our current work lays the groundwork for a clinically relevant therapeutic approach to treating post‐CA syndrome.